Military Topic in the Art of J.A. Atkinson - Skvortsova, Ekaterina A. (Actual Problems of Theory and History of Art, 2013)
The article enriches our knowledge about J.A. Atkinson (1774 or 1776 – 1830) — a so far underrated English artist. He made battle pieces both in painterly and graphic techniques, produced both humble scenes from everyday life of the military and ambitious historical compositions on contemporary subjects. Of special interest is a group of his works connected with Russia — portrait-types made with a certain tint of ethnographic curiosity, which is so characteristic of imperial way thinking.
Keywords: military topic; historical painting; caricature; portrait-type; the problem of commission; Napoleonic wars